Central CRF neurons are not created equal: phenotypic differences in CRF-containing neurons of the rat paraventricular hypothalamus and the bed nucleus of the stria terminalis - Dabrowska, Joanna; Hazra, Rimi; Guo, Jidong; DeWitt, Sarah; Rainnie, Donald (Frontiers in Neuroscience, 2013)
Corticotrophin-releasing factor (CRF) plays a key role in initiating many of the endocrine, autonomic, and behavioral responses to stress. CRF-containing neurons of the paraventricular nucleus of the hypothalamus (PVN) are classically involved in regulating endocrine function through activation of the stress axis. However, CRF is also thought to play a critical role in mediating anxiety-like responses to environmental stressors, and dysfunction of the CRF system in extra-hypothalamic brain regions, like the bed nucleus of stria terminalis (BNST), has been linked to the etiology of many psychiatric disorders including anxiety and depression. Thus, although CRF neurons of the PVN and BNST share a common neuropeptide phenotype, they may represent two functionally diverse neuronal populations. Here, we employed dual-immunofluorescence, single-cell RT-PCR, and electrophysiological techniques to further examine this question and report that CRF neurons of the PVN and BNST are fundamentally different such that PVN CRF neurons are glutamatergic, whereas BNST CRF neurons are GABAergic. Moreover, these two neuronal populations can be further distinguished based on their electrophysiological properties, their co-expression of peptide neurotransmitters such as oxytocin and arginine-vasopressin, and their cognate receptors. Our results suggest that CRF neurons in the PVN and the BNST would not only differ in their response to local neurotransmitter release, but also in their action on downstream target structures.